'Daily Drags' and 'Wannabe Walkers' – Identifying dissatisfied public transport users who might travel more actively and sustainably. Issue 3 (September 2016) - Bösehans, Gustav; Walker, Ian
Abstract: This paper sought better to understand the motives and experiences of bus users, with a view to identifying subgroups who might be persuaded to use healthier and more sustainable modes. Student and staff bus users of a middle-sized university in the UK participated in an online survey, indicating their agreement with a series of statements about local bus services. These statements were combined into independent factors using principal component analysis. Then, using cluster analysis, respondents were split into different types of bus users. The analysis suggested six distinct types, four of which broadly support the captive versus choice user distinction made in earlier studies and two of which were novel. The findings are discussed in relation to previous research and implications for public transport operators and promoters of active travel are outlined. Specifically, the current research suggests that two subgroups of bus users, together accounting for around 41% of this sample, may quite easily be persuaded to travel actively; the other groups, more committed to buses, might have their journeys improved if public transport operators address their concerns. Future research may address the generalisability of the proposed cluster solution and test its applicability in applied settings.